‘Specific’ Interaction of Organic Compounds with Polyethylene - Nikolai V. Nikolenko; Helen S. Smirnova; Irina A. Shmarova (Adsorption Science & Technology)
The ultraviolet absorption spectra of substituted benzenes incorporated in thin films of low-density polyethylene have been studied. Conclusions have been drawn regarding the 'specific' interactions between the polymer and pyridine, N,N-dimethylaniline, nitrobenzene and benzaldehyde based on a comparison of the absorption peak positions of the various molecules when in the gaseous state, dissolved in octane and adsorbed in polyethylene.